Effect of sheep and chicken manure on wheat growth and productivity - Trifa Dh. Saber (Zanco Journal of Pure and Applied Sciences, 2023)
The experiment was conducted during December 2021 to April 2022 at glasshouse of the Department of Biology, College of Education, Salahaddin University-Erbil. The factorial experiment included studying the influence of two types of manure(Poultry and sheep manure) each of them with six levels (0,20,30,40, 50 and 60 )ton ha-1, on vegetative characteristics, number of grain.plant-1, the weight of 100 seeds, leaf chlorophyll contents, protein and nitrogen contents of seeds of wheat cultivar (Seminto) using Randomized complete Design(CRD) using three replicates. The main results were statically analyzed by using Factorial (C.R.D.); each treatment consisted of three replications. Means were compared using the L.S.D. test at a p-value of 0.05 for plant features in the side glasshouse and 0.01 for chemical characteristics. poultry manure and sheep manure by soil application significantly increased plant height.plant-1, number of leaves,plant-1, number of tillers,plant-1, flag leaf area, shoot system dry weight (g), chlorophyll contents of leaves, grain number.plant-1 and weight of I00 grain.